1970
DOI: 10.1128/aem.20.1.156-159.1970
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Fermentative, Gram-Negative Bacilli Isolated from Clinical Specimens

Abstract: Morphological and physiological characterization of 12 Aeromonas strains isolated from clinical specimens demonstrated several important diagnostic features. These included polar arrangement of the flagella; production of oxidase, deoxyribonuclease, amylase, gelatinase, and lipase; lack of ornithine decarboxylase; and sensitivity to polymyxin. Awareness of these features should result in more frequent differentiation of aeromonads from the physiologically similar members of the genus Plesiomonas and the lateor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The pattern of antibiotic resistance in both species resembled closely that found in clinical strains of A . hydrophila (Gilardi et al 1970) and contrasts with the pattern of more extensive resistance found in strains of A . liquefaciens isolated from fish in Japan (Aoki et al 1971).…”
Section: Discussionmentioning
confidence: 67%
“…The pattern of antibiotic resistance in both species resembled closely that found in clinical strains of A . hydrophila (Gilardi et al 1970) and contrasts with the pattern of more extensive resistance found in strains of A . liquefaciens isolated from fish in Japan (Aoki et al 1971).…”
Section: Discussionmentioning
confidence: 67%
“…Carbon utilization and nitrate reduction by the strain ISO2-3 were evaluated and compared to the data reported previously for A. hydrophila, A. punctata, and A. caviae (Gilardi et al, 1970) ( Supplemental Table II). The carbon utilization pattern of the strain ISO2-3 was closer to one of A. hydrophila than those of A. punctata and A. caviae.…”
Section: Characterization Of the Isolated Strain Iso2-3mentioning
confidence: 99%